The role of endoscopic retrograde cholangiopancreatography in choledochal cysts and/or abnormal pancreatobiliary junction in children - Drabek, Jiri; Keil, Radan; Stovicek, Jan; Lochmannova, Jindra; Hlava, Stepan; Snajdauf, Jiri; Rygl, Michal; Nevoral, Jiri (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : Biliary cysts with an abnormal pancreatobiliary junction are one of the most common pancreatobiliary malformations. The main symptom is cholestasis; endoscopic retrograde cholangiopancreatography (ERCP) plays a key role in diagnosis. Aim : Retrospective evaluation of ERCP performed to diagnose abnormalities of the pancreatobiliary junction. Material and methods : We retrospectively evaluated ERCP performed to diagnose abnormalities of the pancreatobiliary junction, mainly choledochal cysts, in 112 children between 1990 and 2011. Results : We performed 112 examinations of 50 children with abnormal pancreatobiliary junction and choledochal cysts (15 males and 35 females, average age: 5 years, range: 1 month – 15 years). Cysts were associated with a common channel in 37 (74%) cases, were not associated with a common channel in 9 (18%) cases, and in 3 (6%) cases the common channel lacked cysts. We performed endoscopic papilla sphincterotomy on 33 (66%) patients; endoscopic drainage was performed 62 times, including 17 patients without papilla sphincterotomy. In 15 (30%) cases, we only performed sphincterotomy. Extraction of lithiasis was done in 2 (4%) cases. Both ERCP and magnetic resonance cholangiopancreatography (MRCP) were performed on 13 patients. There was concordance of the choledochal cyst and of the type of cyst in both methods; however, common channels could not be observed by MRCP. There was 1 serious complication (perforation after sphincterotomy) and 11 (9%) mild adverse events. Conclusions : When performed at an expert centre, ECRP is a safe and reliable procedure for children with choledochal cysts and/or an abnormal pancreatobiliary junction. Endoscopic retrograde cholangiopancreatography remains a reasonable alternative because MRCP has a limited ability to diagnose the precise anomalies of the pancreatobiliary junction and has no therapeutic capabilities.